An Improved Model Opportunity Recognition for Graduate Entrepreneur Opportunity Using Web Content Analytics (S/O 13798) - Abu Bakar, Muhamad Shahbani; Yasin, Azman; Ta'a, Azman; Hassan, Syahida (UUM, 2020)
The ability to recognize and develop an opportunity into a venture defines an entrepreneur. Factors such as prior knowledge, cognitive and creative capabilities are shown to affect opportunity recognition in entrepreneurs. Prior knowledge in areas such as customer problems, ways to serve the market, and technology has been shows in varoius studies to be a factor that facilitates entrepreneurs to identify and recognize opportunities especially in product innovation. At the start of any product innovation process, many ideas are essential; the higher quality the better to increase the probability of success. Therefore, the process and support to enable high quantity and quality creative ideation for new products is critical for product innovation. Research on models to support new product ideation for large firms and professionals are numerous over the years while the entrepreneurs are mostly neglected. There is need to research on support for product innovation ideation specifically for graduate entrepreneur; the former requires existing cooperative computer-assisted ideation models that have limited applicability for the graduate entrepreneur; the former requires existing cooperative users and is not suited for new graduate entrepreneurs. The specific aims of the study are to identify relevant elements and guidelines that influence innovative product ideation, contruct improved computer assisted model of the of product innovation idea generation and evaluate usability of proposed model through expert review and prototyping. This research will be conducted based on quantitative and data mining consists of problem identification, solution design and evaluation. These stages are not expected to be sequential but can go back forth as the research progresses. This model is expected to enable graduate entrepreneurs to generate more business ideas that are more innovative and viable.